A Study on Safety and Efficacy of Sodium-glucose Cotransporter-2 Inhibitors as Adjuvant to Insulin Add-on Therapy in Uncontrolled Type 2 Diabetic Patients - Andhuvan, G. (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Inhibitors of sodium-glucose cotransporter-2 (SGLT-2) are proposed as a novel approach for the management of type 2 diabetes mellitus. SGLT-2 inhibitors have major advantages in terms of reducing HbA1c, blood sugar levels, body weight, and blood pressure and may potentially reduce the cardiovascular (CV) risk. The objective of the study is to assess the safety and efficacy of SGLT-2 inhibitors as an adjuvant to insulin add-on therapy in uncontrolled type 2 diabetic patients. Materials and Methods: The study was conducted in 100 patients with uncontrolled type 2 diabetes mellitus. 50 patients were received SGLT-2 inhibitor add-on therapy with gliclazide-metformin and insulin, and remaining 50 patients were received insulin add-on therapy with gliclazide metformin. The changes in fasting blood sugar (FBS), glycosylated hemoglobin (HbA1c), weight, body mass index (BMI), blood pressure, and CV risk of diabetic patients before the initiation of add-on therapy and after 6 months follow-up were measured. Diabetes-related complications such as foot ulcer, hypoglycemic episodes, and urinary tract infections were documented. Results: Patients on SGLT-2 inhibitors as adjuvant to insulin add-on therapy show better glycemic control, reduction in weight, BMI, blood pressure, and CV risk. In patients with SGLT-2 inhibitors add-on therapy, these were changes from baseline HbA1c (2.333%), FBS (82.97 mg/dL), and BMI (2.049 kg/m2). In hypertensive patients, mean reduction in systolic blood pressure (SBP) and diastolic blood pressure (DBP) was 15.12 mmHg and 6.40 mmHg, respectively. In non-hypertensive patients, mean reduction in SBP and DBP was 7.60 mmHg and 1.88 mmHg, respecively. The mean CV risk reduction was 6.046%. Among 50 patients, 3 developed urinary tract infection (UTI) and 1 developed hypoglycemia. In insulin add-on therapy patients, these were changes from baseline HbA1c, FBS, and BMI 1.029%, 39.98 mg/dL, and −1.584 kg/m2, respectively. In hypertensive patients, SBP was 10.84 mmHg and DBP was 4.120 mmHg, and in non-hypertensive patients, mean reduction in SBP and DBP was −3.080 mmHg and −3.36 mmHg. The mean CV risk reduction was 0.866%. Of 50 patients, 5 developed UTI, 9 developed hypoglycemia, and 3 developed foot ulcer. Conclusion: SGLT-2 inhibitors are safe and effective for treatment in uncontrolled T2DM. The use of SGLT-2 inhibitors is very effective in glycemic control (reduction in HbA1c and FBS). The non-glycemic effects of SGLT-2 inhibitors include reduction in weight, BMI, and blood pressure. Therefore, glycemic and non-glycemic benefits contribute to an overall reduction in CV risk.